Analysis of the Consumption Behavior of Gymnastics Activists in Sukosari Village and its Impact on Family Finances Islamic Economic Perspective - Zia Lutfiatur Rosyida; Ely Masykuroh (Journal of Social Research, 2022)
This study aims to analyze the consumption behavior of gymnastics activists in Sukosari Village and their impact on their family finances. The behavior shown is to be willing to spend more money to buy gymnastics equipment that is quite expensive and other non-urgent consumption which results in an increase in the family's financial budget. The research method used is descriptive qualitative with a field research approach based on data analysis obtained from interviews and observations. The results obtained from this study are: 1) The consumption motives of housewives of gymnastics activists in Sukosari Village are based on needs, and maslahat, and a small part of it is followed by desire, ego, and individualism. It is these motives based on desires and egos that are not advocated in Islam. 2) Most of the mothers of gymnastics activists consume something especially gymnastics needs only if it is urgent. Others are based on the latest model they like. 3) Some gymnastics activists have a savings ratio below 10% or below the minimum percentage of savings ratio. This shows that gymnastics activities and other non-urgent consumption lead to a reduced level of savings in the family finances of gymnastics activist mothers.